Evaluation of BOX-PCR and ERIC-PCR as Molecular Typing Tools for Pathogenic Leptospira - Lesley, Maurice Bilung; Chai, Fung Pui; Lela, Suut; Kasing, Apun (Hindawi Publishing, 2018)
In the last decades, leptospirosis had gained public health concern due to morbidity and mortality rates caused by pathogenic Leptospira. The need for rapid and robust molecular typing methods to diﬀerentiate this zoonotic pathogen is of utmost importance. Various studies had been conducted to determine the genetic relatedness of Leptospira isolates using molecular typing methods. In this study, 29 pathogenic Leptospira isolates from rat, soil, and water samples in Sarawak, Malaysia, were characterized using BOX-PCR and ERIC-PCR. The eﬀectiveness of these two methods with regard to the ease of interpretation, reproducibility, typeability, and discriminatory power was also being evaluated. Using BOX-PCR, six clusters and 3 single isolates were deﬁned at a genetic distance percentage of 11.2%. ERIC-PCR clustered the isolates into 6 clusters and 2 single isolates at a genetic distance percentage of 6.8%. Both BOX-PCR and ERIC-PCR produced comparable results though the discriminatory index for ERIC-PCR (0.826) was higher than that for BOX-PCR (0.809). From the constructed dendrogram, it could be summarized that the isolates in this study were highly heterogeneous and genetically diverse. The ﬁndings from this study indicated that there is no genetic relatedness among the pathogenic Leptospira isolates in relation to the locality, source, and identity, with some exceptions. Out of the 29 pathogenic Leptospira isolates studied, BOX-PCR and ERIC-PCR successfully discriminated 4 isolates (2 isolates each) into the same cluster in relation to sample sources, as well as 2 isolates into the same cluster in association with the sample locality. Future studies shall incorporate the use of other molecular typing methods to make a more thorough comparison on the genetic relatedness of pathogenic Leptospira